Обгрунтування безпечності використання катіонних повехнево-активних антисептиків у складі препаратів на основі нанодисперсного кремнезему для проведення ентеросорбції - Pentyuk, A. A.; Viltsanuk, A. A.; Khutoryanskiy, M. A.; Ilchenko, A. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The parameters of sorbtion interaction of detergent antiseptics (aethonium, decamethoxinum) are studied - in the sorbtion composition Flotoxan, with human serum albumin and by them complex system. Findings showed that the use of the developed composition which contains detergent antiseptics in mass correlation 1,5% is experimentally grounded, safe and expedient for the enterosorbtion at acute abdominal surgical pathology